2016
DOI: 10.1038/tp.2016.52
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating the therapeutic effects of environmental enrichment and exercise in a mouse model of anxiety with cognitive impairment

Abstract: Clinical evidence indicates that serotonin-1A receptor (5-HT1AR) gene polymorphisms are associated with anxiety disorders and deficits in cognition. In animal models, exercise (Ex) and environmental enrichment (EE) can change emotionality-related behaviours, as well as enhance some aspects of cognition and hippocampal neurogenesis. We investigated the effects of Ex and EE (which does not include running wheels) on cognition and anxiety-like behaviours in wild-type (WT) and 5-HT1AR knock-out (KO) mice. Using an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 71 publications
0
31
1
Order By: Relevance
“…However, it would also be important to contrast our environmental enrichment protocol with that of Gapp et al (2016), which provided running wheels. Our laboratory, and others, have demonstrated dissociable effects of environmental enrichment and running on behavior and hippocampal gene expression (Grégoire et al, 2014;Mustroph et al, 2016;Rogers et al, 2016;Zajac et al, 2010); thus, it would be reasonable to speculate that offspring hippocampal GR expression is not influenced under our experimental conditions.…”
Section: Paternal Environmental Enrichment Had No Influence On F1 Offmentioning
confidence: 65%
See 1 more Smart Citation
“…However, it would also be important to contrast our environmental enrichment protocol with that of Gapp et al (2016), which provided running wheels. Our laboratory, and others, have demonstrated dissociable effects of environmental enrichment and running on behavior and hippocampal gene expression (Grégoire et al, 2014;Mustroph et al, 2016;Rogers et al, 2016;Zajac et al, 2010); thus, it would be reasonable to speculate that offspring hippocampal GR expression is not influenced under our experimental conditions.…”
Section: Paternal Environmental Enrichment Had No Influence On F1 Offmentioning
confidence: 65%
“…Environmental enrichment (EE) is an experimental paradigm that has been shown to limit behavioral, cellular and molecular pathologies in various disease models, including models of stress (Chekmareva et al, 2014;Renoir et al, 2013;Rogers et al, 2016). EE rescues the depression-like phenotype and corrects HPA-axis dysregulation in a mouse model of alcohol withdrawal .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the use of different developmental deficits is greatly encouraged, as this will assist in developing effective therapeutic interventions for individuals afflicted by such disorders. Previous literature has demonstrated independent effects of WR or EC on adult neurogenesis, learning and memory, or anxiety-like behaviors in a genetic mouse model of anxiety 53 . The robustness of these two interventions and the synergistic effect of EC to sustain the short-term effects of increased WR-induced benefits ( i.e.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, Choi et al found that exercise could delay cognitive decline by enhancing neurogenesis and increasing BDNF expression in the context of VaD [37]. Rogers et al found exercise (Ex) and EE (without exercise) had different effects in a mouse model of anxiety with cognitive impairment, and corrected long-term spatial memory deficits are related to Ex, but not the 2 other parts of EE [38]. Sozda et al demonstrated that exposing TBI rats to any of the 3 components individually may be more advantageous than no enrichment, but only exposure to typical EE yields optimal benefits.…”
Section: Discussionmentioning
confidence: 99%